Sound Visualization and Manipulation. - Kim, Yang-Hann (Wiley, 2013)
Unique in addressing two different problems - sound visualization and manipulation - in a unified way Advances in signal processing technology are enabling ever more accurate visualization of existing sound fields and precisely defined sound field production. The idea of explaining both the problem of sound visualization and the problem of the manipulation of sound within one book supports this inter-related area of study. With rapid development of array technologies, it is possible to do much in terms of visualization and manipulation, among other technologies involved with the spatial dis.